Community Perception Of Gender Equality In The Family : M Taufik, Hasnani, Suhartina - Muhammad Taufik; Suhartina Suhartina; Hasnani Hasnani (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2022)
The community has an identity that interacts with each other and has each individual, in the community there is a small group called a family consisting of husband, wife and children, they work together to create a sakinah, mawaddah and warahmah family, but in the village of Mattiro Ade the system in the family still believes that the husband is responsible for working to earn a living and the wife is responsible for taking care of the domestic work. The purpose of this study was to find out gender in the family and describe the form of gender in the family in Mattiro Ade Village. This study uses descriptive qualitative methods and uses data collection techniques of observation, interviews and documentation. The results of the study show that, the community's perception of gender in the family in Mattiro Ade Village, the gender system is very good to run in the family because it teaches us to work together and answer questions about the gender of the people of Mattiro Ade Village in their daily life the concept of gender because there are no limits in carrying out their roles. domestic or public, gender is mutual understanding, mutual responsibility, sharing with love, for the sake of household sustainability, while gender harmony in the family is the division of roles is a concept that is carried out because they have each public affairs such as earning a living to meet the needs of the family and the wife is responsible for working on domestic affairs, such as taking care of housework, cooking, cooking and caring for children, but there is no limit for husband and wife if they want to play a role in both roles.